A Critical Review on Recent Development of Techniques and Drug Targets in the Management of Breast Cancer - Buumba, Betty M.; Bhardwaj, Shweta; Kaur, Paranjeet (Mini Reviews in Medicinal Chemistry, 2021)
Background: The most documented illness affecting women overall is breast malignant growth. Since breast cancer disease is the most widely recognized threat in women, Since breast cancer disease is the most widely recognized threat in women, this review was done to provide data on the ongoing advancements in the medication focused on in the breast cancer regimen. Over the previous decades, it has been seen that different progressions have been made in the disclosure of new medications and treatments for treating breast malignancy and this is a direct result of the improved comprehension of the biologic heterogeneity of breast cancer, which has likewise permitted the advancement of increasingly compelling ways to deal with treating breast cancer. Methods: We searched the scientific database using relevant keywords. Among the searched literature, only peer-reviewed papers were collected, which address our questions. The retrieved quality papers were screened and analyzed critically. The key findings of these studies are included along with the importance. Results: The research in this review particularly includes the anti-breast cancer drugs, which accountfor the top largest market by sales in the pharmaceutical industry. Apart from these, natural and innovative therapies have emerged leading to better management of breast cancer. Conclusion: These recent developments have contributed to a more efficient and specific treatment protocol in breast cancer patients. Moreover, further investigation should be done in improving results for all the patients with breast cancer disease, particularly individuals who have advanced breast cancer and the issue of drug resistance, which also poses a threat to the successful development of targeted therapy in various subtypes of breast cancer, must also be considered.
Keywords: natural product therapy